Teams in Transition: A Three-Wave Longitudinal Study of Reflection, Implicit and Explicit Coordination and Performance Improvements - Konradt, Udo; Schippers, Michaéla C.; Krys, Sabrina; Fulmer, Ashley (Frontiers in Psychology, 2021)
Research has shown that team reflection is a critical transition process for coordination processes and team performance, but our understanding of its dynamics and relationship to action processes and performance is incomplete. The goal of the present study was to examine the long-term change in reflection in teams over time and explore whether these changes are related to implicit and explicit coordination processes and performance improvement. Drawing on the recurring phase model of team processes and team reflexivity theory, we hypothesized that team reflection is at least stable or increases over time for dissimilar tasks, that reflection trajectories are positively associated with implicit and negatively associated with explicit coordination in the later phases, and that implicit coordination mediates the relationship between team reflection and performance improvement. This model was tested in a three-wave longitudinal study (N = 175 teams) over a two-month period. Results from growth curve modeling and structural equation modeling provided support for our hypotheses.